Does nailfold capillaroscopy help predict future outcomes in systemic sclerosis? A systematic literature review - Paxton, Dolcie; Pauling, John D. (Seminars in arthritis and rheumatism, 2018)
Nailfold capillaroscopy (NC) is an important diagnostic tool in systemic sclerosis (SSc). Confirmation of NC as a prognostic factor could facilitate earlier intervention and slow disease progression in SSc. We undertook a systematic literature review to evaluate the prognostic value of NC in predicting SSc disease progression. Standardised searches of EMBASE and MEDLINE were undertaken to identify longitudinal studies of adult subjects with SSc reporting the prognostic value of NC for any aspect of disease progression and/or survival. Non-English, non-original research, animal studies, non-adult studies and non-full length reports were excluded from the analysis (PROSPERO 2017:CRD42017071719). Wide heterogeneity in study design, prognostic factor measurement and study outcomes necessitated a qualitative data synthesis. The “QUality In Prognosis Studies” (QUIPS) risk-of-bias tool was used to assess study quality. Study selection, data extraction and risk-of-bias assessment were each undertaken independently by 2 reviewers and consensus reached where necessary. Of 942 retrieved articles, 18 studies fulfilled the inclusion criteria. The majority of studies (17/18, 94%) reported positive associations between baseline NC appearances (using a variety of qualitative, semi-quantitative and quantitative NC endpoints) and clinical outcomes including digital ulcer (DU) occurrence/healing, survival, disease progression (using domains of Medsger disease severity scale), calcinosis, skin progression, pulmonary arterial hypertension (PAH), and/or a composite analysis of “cardiovascular events”. Application of the QUIPS tool identified a moderate-high risk of potential bias in 6/18 studies for study participation, 3/18 studies for study attrition, 10/18 for prognostic factor measurement, 5/18 for outcome measurement, 13/18 for confounders and 13/18 for statistical analyses. Study quality limited the strength of the conclusions drawn from these studies. The most important source of potential bias across the studies was insufficient adjustment for potential confounders; such as existing DU disease in studies evaluating future DU occurrence. Recent work suggests NC evolution is an important predictor of disease progression in SSc. High levels of potential bias relating to study confounding and statistical analysis make it difficult to draw conclusions regarding the prognostic role of NC in SSc. There is strong evidence supporting an association between NC abnormalities (particularly capillary loss) and disease severity (particularly vascular manifestations such as DU, calcinosis and PAH). Evolution of NC appearances may represent a more important predictor of disease progression which could have important implications for the future use of NC in the routine longitudinal assessment and management of SSc.